2014
DOI: 10.2478/bvip-2014-0099
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin-like immunoreactive primary sensory neurons supplying the porcine adrenal glands in physiological conditions and after adrenalectomy

Abstract: Retrograde neuronal tracing, using fast blue, in combination with a single-labelling immunofluorescence technique, was applied to determine whether somatostatin (SOM) participates in sensory innervating of the porcine adrenal glands in physiological conditions and after adrenalectomy. In control animals, SOM-like immunoreactive neurons comprised 7.0 ± 0.7% of adrenal gland-projecting cells in dorsal root ganglia (DRG) at neuromeres Th6-7 and 6.5 ± 1.2% at neuromeres Th12-14. After adrenalectomy the percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…On the other hand, neuronal transection following partial stomach resection also triggered significant changes in SOM-LI immunoreactivity, which is in agreement with previous findings on the influence of axotomy on an increase in SOM expression [ 31 ]. In contrast, other authors reported decreased expression of SOM after neuronal injury [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, neuronal transection following partial stomach resection also triggered significant changes in SOM-LI immunoreactivity, which is in agreement with previous findings on the influence of axotomy on an increase in SOM expression [ 31 ]. In contrast, other authors reported decreased expression of SOM after neuronal injury [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…An increase in the population of SOM-LI neurons in animals of the ASA group correlates well with the fact that somatostatin exerts antinociceptive/analgesic and anti-inflammatory effects during inflammatory processes [ 14 , 31 ], including GI inflammatory pathologies [ 13 ]. Recent evidence demonstrates significant changes in SOM expression in idiopathic inflammatory bowel diseases [ 16 ], Crohn's disease, ulcerative colitis [ 17 ], chemically induces colitis [ 29 ], proliferative enteropathy, and chemically driven inflammation of porcine descending colon [ 15 ].…”
Section: Discussionmentioning
confidence: 98%